Service Redesign General Sharia Insurance – Renewal Account (International Journal of Applied Research in Management and Economics, 2020)
On present day, sharia insurance industry is having a significant growth yearly. The annual growth is around 3%-5% and potentially could achieve 20% yearly in growth. This research used the current existing service design element problems in sharia insurance industry as the basis for this research. Steps taken in this research is by using service quality in order to get the needs of the customer. The aims of this research are to design the renewal service of insurance in accordance with the customer needs and provide alternative solutions to the problems by conducting the research in one of sharia insurance companies in Indonesia. Further purpose of this study is to implement the renewal service design recommendation that match the customer needs. The methods used in this research are TRIZ with service quality and service blueprint in seeking the current and improved condition. This research also uses service design method as the basic theory in creating high quality service system in accordance to customer requirements and service redesign method for recreating an improved version of the service. The output of this research is the improved service design recommendation mapped in service blueprint. Furthermore, the research also gives alternative solutions on the existing problem which can be applied to the service.